Advertising as a Mirror of Cultural Stereotypes: Opportunities and Risks of Its Use in Teaching Russian as a Foreign Language - Khalilova, Dilnoza Ubaydullayevna; Nasiba Bakhritdinovna, Azizova (The Lingua Spectrum, 2026)
This article examines advertising as a reflection of cultural stereotypes and its didactic potential in teaching Russian as a Foreign Language (RFL). As a component of mass culture, advertising conveys values, norms, and patterns of behavior characteristic of a particular society. The author analyzes the possibilities of using advertising texts and video commercials in the educational process, including the development of intercultural competence, the formation of critical thinking skills, and the expansion of students’ lexical and grammatical knowledge. Particular attention is paid to the risks associated with reinforcing simplified stereotypes, distorting cultural reality, and causing cultural shock. Methodological recommendations are proposed for integrating advertising materials into RFL teaching practice, taking into account students’ language proficiency levels and cultural sensitivity.